POLA CORPORATE SOCIAL RESPONBILITY (CSR) DALAM PEMBERDAYAAN USAHA KECIL KERAJINAN ECENG GONDOK DI KECAMATAN BANYUBIRU - Witjaksono EH; Diana Puspitasari (Universitas Semarang, 2016)
The high awareness of the importance of practicing Corporate Social Responsibility (CSR) has become a global trend and lifestyle company with the increasingly widespread concern in the interests of stakeholders. With the sophistication of information technology and market openness without limits brought against company policy to be more serious in considering Corporate Social Responsibility (CSR).Water hyacinth handicraft industry is one business that is quite well known in the district Banyubiru, Semarang District and is one of the featured products at Semarang district that can contribute to economic growth in the district of Semarang. Water hyacinth handicraft industry in the District Banyubiru, Semarang regency should be developed through Corporate Social Responsibility (CSR).Corporate Social Responsibility (CSR) will be highly beneficial for SMEs if the water hyacinth program implemented on target and in line with expectations and desires required by craftsmen. So we need good communication between the giver and the recipient of its Corporate Social Responsibility (CSR).